Fetal growth restriction promotes physical inactivity and obesity in female mice - Baker, M S; Li, G; Kohorst, J J; Waterland, R A (International Journal of Obesity, 2015)
Background: Environmental exposures during critical periods of prenatal and early postnatal life affect the development of mammalian body weight regulatory mechanisms, influencing lifelong risk of obesity. The specific biological processes that mediate the persistence of such effects, however, remain poorly understood. Objective: The objectives of this study were to determine the developmental timing and physiological basis of the obesity-promoting effect previously reported in offspring of obese agouti viable yellow ( A vy /a ) mothers. Design: Newborn offspring of obese A vy /a and lean ( a/a ) mothers were cross-fostered shortly after birth to study separately the effects of in utero or suckling period exposure to A vy /a dams. Body composition, food intake, physical activity and energy expenditure were measured in offspring shortly after weaning and in adulthood. Results: Offspring of obese A vy /a dams paradoxically experienced fetal growth restriction, which was followed by adult-onset obesity specifically in females. Our main analyses focused on wild-type ( a/a ) offspring, because a subset of adult A vy /a offspring contracted a kidney disease resembling diabetic nephropathy. Detailed physiological characterization demonstrated that, both shortly after weaning and in adulthood, female wild-type mice born to A vy /a mothers are not hyperphagic but have reduced physical activity and energy expenditure. No such coordinated changes were detected in male offspring. Mediational regression analysis of our longitudinal data supported a causal pathway in which fetal growth restriction persistently reduces physical activity, leading to adult obesity. Conclusions: Our data are consistent with several recent human epidemiological studies showing female-specific effects of perinatal nutritional restriction on later obesity, and provide the novel mechanistic insight that this may occur via permanent and sex-specific changes in one’s inherent propensity for physical activity.